Amine modified sodium alginate: Synthesis, characterization and in vivo evaluation in rainbow trout (Oncorhynchus mykiss) - Samira Salarvand; Seyed Amir Hossein Jalali; Nasrollah Mahboobi Soofiani; Alireza Allafchian (Carbohydrate Polymer Technologies and Applications)
Alginate is a natural linear anionic biopolymer abundantly found in the seabed. Alginate becomes an adequate option as a diet improver or drug/gene carrier through chemical modification processes and changes in its structure. This study modified a simple sodium alginate by oxidation and reductive amination processes. The characteristics of modified sodium alginate were evaluated by FTIR, XRD, zeta potential, FE-SEM, EDX, and MAP analysis. Its cytotoxicity was evaluated using an MTT assay. Finally, its effects were assessed orally in rainbow trout (3 ± 0.3 g) for 6 weeks at 2 levels (2.5 and 5 g kg-1). The characterization showed that the chemical modification process was successful, and amine groups were incorporated into the alginate structure. The amount of amine added to modified sodium alginate was 2.53 % based on EDX. MTT results showed no cytotoxicity for modified alginate. The in vivo results showed that amine-modified alginate treatments significantly increased non-specific immune parameters, including lysozyme activity, alternative complement activity, and serum bactericidal activity, and also enhanced intestinal bacterial population compared with the control and simple alginate treatments (P < 0.05). Administration of 2.5 and 5 g kg-1 modified alginate significantly increased FCR (0.84±0.01 and 0.83±0.04, respectively) and other growth parameters compared with other experimental groups (P < 0.05). Also, after being challenged by ozone, amine-modified alginate fish groups showed the highest relative percent survival (RPS) values (75 %, 90 %). This improvement can be attributed to the modified alginate's nature and the amine groups' role in its structure. Therefore, amine-modified alginate can be suggested as an immunostimulant.